The Role Of Digitalization In Operational Efficiency Case Study On Seganex Footwear SMEs in Mojokerto City - Rivaldo Kurniawan; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (Abadi Institute, 2026)
The development of digital technology offers opportunities for MSME actors to enhance operational efficiency and business competitiveness. This case study aims to analyze the role of digitalization in improving operational efficiency at the footwear MSME “Sepatu Seganex” in Mojokerto City. The study employed a qualitative descriptive method through field observations, interviews with the owner, and documentation of the production process. The findings indicate that the implementation of digitalization—covering digital financial recording, order management systems, digital marketing, and the use of marketplaces—significantly improves time efficiency, reduces operational costs, and increases productivity. The main challenges include limited digital human resources, initial technology adoption costs, and suboptimal internet access. This study contributes to MSME literature related to digital transformation strategies in the local manufacturing sector.